Cost-Benefit Analysis of Buffalo Milk Production in India - Kaur, Napinder; Iqubal, Md Asif; Toor, Jasdeep Singh; Abusaad, Md (Journal of Buffalo Science, 2024)
Context: The vast resource of Indian livestock played an important role in improving the socio-economic conditions of people in rural areas. Dairying has provided strong support to stabilise the Indian economy by ensuring a certain degree of diversification and flexibility. Aim: The present study aims to analyse the costs and returns from buffalo milk production in the Punjab state of India to know about the viability of the dairy business. Methods: The present study is based on primary data collected through a detailed schedule from 420 dairy farmers belonging to different farm size categories (landless households, large, medium, small, and marginal farmers) from 21 villages situated across three different agro-climatic zones of Punjab state in 2019. A multi-stage sampling technique has been used to select the villages and dairy farmers in the study area. Key Results: The study has revealed that the total costs of buffalo milk production are ₹180.16 per day per milch buffalo. The sale of fluid milk constitutes a major component of gross returns. The net returns are calculated as ₹6.42 per litre from buffalo milk production in rural Punjab. Implications: Economic analysis of dairy farming is very important to know about the economic viability of dairy enterprises. The profitability from dairying depends upon the milk yield of dairy animals, the sale price of milk, and the cost involved in dairying. Adequate knowledge of the cost involved in dairying is important as it can be used for policy-making and also for providing incentives to dairy farmers.